Biomedical waste management at tertiary level hospital–Rajindra Hospital [Government Medical College], Patiala-A situational analysis - Virender Verma; M.L. Sharma; Simmi Oberoi; Amarjit Singh (International Journal of Medical Research and Review, 2016)
Background: Studies in India and other developing countries has shown poor practice of Biomedical waste management [BMW]. Hence this study was undertaken to situation of BMW in our hospital, to identify the gaps and to take necessary steps for rectification.Materials & Methods: This was an observational descriptive hospital based cross sectional study. All sites where biomedical waste is generated, were visited during 3 months. The collection point was visited continuously for a week after collection of data from sites. The data, thus generated, were compiled, analyzed and inferences were drawn.Results: It showed that all Indoor site [100%] had a system for segregation and appropriate display as per guidelines was present. In OPDs the buckets were kept according to the waste type being generated i.e. not all colored buckets were kept. At 10% of sites the display was not to the standards desired. Among the remaining sites, 5 sites i.e. of sites the color coding guidelines were not followed. 37 such staff members recently assigned were found untrained.Conclusions: This study revealed that there is the need for the training programme and proper implementation of guidelines for BMW.